2017
DOI: 10.1007/s40271-017-0273-5
|View full text |Cite
|
Sign up to set email alerts
|

Light Chain (AL) Amyloidosis: The Journey to Diagnosis

Abstract: BackgroundLight chain (AL) amyloidosis is a rare, complex disease associated with significant morbidity and mortality. Delays in diagnosis are common and may have detrimental consequences on patients’ prognosis. Too little is known regarding the patient journey to diagnosis.ObjectiveThe objective of this study was to describe the patient-reported journey to a correct diagnosis for AL amyloidosis.MethodsUsing a mixed-methods approach, data were collected from clinician (n = 4) and patient (n = 10) interviews an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
93
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(100 citation statements)
references
References 11 publications
4
93
0
3
Order By: Relevance
“…Despite these advances, most patients with peripheral amyloidosis present with clinically advanced disease at which time significant tissue amyloid has been deposited and organ damage is manifest. In almost all cases, a diagnosis of amyloidosis results, albeit belatedly, from symptoms of cardiomyopathy, renal insufficiency, or peripheral neuropathy (28,29). For these patients, removal of amyloid deposits may stabilize or improve organ function.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these advances, most patients with peripheral amyloidosis present with clinically advanced disease at which time significant tissue amyloid has been deposited and organ damage is manifest. In almost all cases, a diagnosis of amyloidosis results, albeit belatedly, from symptoms of cardiomyopathy, renal insufficiency, or peripheral neuropathy (28,29). For these patients, removal of amyloid deposits may stabilize or improve organ function.…”
Section: Discussionmentioning
confidence: 99%
“…Patient may associate these symptoms with the ageing process or attribute them to other more prevalent chronic conditions. 27 These non-specific symptoms may not raise immediate concern for patients contributing to delays in seeking medical attention. Even in the presence of distinctive, but uncommon symptom, as purpura, 29 proper diagnosis of amyloidosis may be missed showing how difficult CA diagnosis could be.…”
Section: Protean Diseasementioning
confidence: 99%
“…Due to its non‐specific symptoms, delays in the diagnosis and misdiagnosis of AL amyloidosis are common 13 . McCausland et al 19 surveyed 341 patients and found that 62.5% (n = 213) were seen by greater than 3 physicians before receiving a definitive diagnosis. Another study by Lousada et al 20 utilized data from an online survey to describe the patient experience and journey.…”
Section: Introductionmentioning
confidence: 99%